Campaña para prevenir el incremento de casos de anorexia y bulimia entre la juventud estudiantil de la ciudad de Guayaquil - Cedillo Jurado, Tatiana Del Rosario (2010)
Among the habitants of the Guayaquil City, there is not enough information about eating disorders. These ills can affect anyone, regardless of their socio-economic level, age or gender. This project will develop these issues through graphic pieces, and it will produce a documentary with all the necessary information related to these disorders, including real testimonials from patients and doctors that will give us their point of view about the subject from its origins to the present. Anorexia and bulimia are eating disorders that lead us to increase and decrease weigh. More and more people are having these disorders but the symptoms are different in each one, for that we will informed the different aspects psychical, emotional and physics, and you will be able to recognize if anyone have this problem. Finally, this Project will help to inform and guide young people to share their knowledge to prevent further cases of disorders in the city.